(untitled) (Circe de clásicos y modernos, 2018)
Complementary to the paper about the life and works of Joseph Haydn, we present this time an analysis of his vocal music in relation with classic antiquity: Acide(1762) (opera), Philemon und Baucis (1773) (Singspiel) and Orfeo ossia l’anima del fi losofo(opera) composed in 1791 for being premiered in London. A depiction of his cantata Arianna in Naxos is also provided, as it can be treated as an advance of the type of vocal expression called Lied, considered the utmost creation of romanticism. The elaboration of Haydn’s opera works with mithological contents is situated in the context of his total production within the opera genre.